2009
DOI: 10.2106/jbjs.h.01108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Self-Reports and Parent Proxy-Reports of Function and Quality of Life of Children with Below-the-Elbow Deficiency

Abstract: Although the absolute differences are small, children with a unilateral congenital below-the-elbow deficiency report better upper-extremity function and quality of life than their parents perceive, but they may also be experiencing more pain. Factors influencing parent-child agreement on measures of quality of life include age and use of a prosthesis. Parents' reports of function may provide a helpful counterbalance to children's and adolescents' reports, but because quality of life is subjective by nature, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 20 publications
8
78
3
Order By: Relevance
“…Many studies have been performed to evaluate functioning in daily life of children with UCBED with or without prosthesis [1,2,6,[15][16][17][18]. However, our study is the first with a longitudinal and observational design starting in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been performed to evaluate functioning in daily life of children with UCBED with or without prosthesis [1,2,6,[15][16][17][18]. However, our study is the first with a longitudinal and observational design starting in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that parents underestimated sports/physical function and happiness compared with the patient reports; this has been shown for other congenital conditions as well. 58 Anatomical variation in vascular structures engenders concern about potential effect of these anomalies on the viability of the vascular anastomoses and survival of the transferred toe. A review of toe-to-hand transfers in congenital hand differences, however, found an average transplant survival rate of more than 96%.…”
Section: Syndactyly and Web Contracturementioning
confidence: 99%
“…In the present study, we collected ratings from children themselves or their parents/guardians if the children did not meet the required age or developmental level for self-scoring. Though differences in the perception and rating of bimanual performance are known to exist between children and their parents/guardians (Majnemer et al, 2008;Sheffler et al, 2009;Gates et al, 2010), the present study was not designed to investigate such differences. Investigations of using a different study design may also enable differentiation according to age, sex, and diagnosis.…”
Section: Discussionmentioning
confidence: 99%